Taxation Provisions for Multinational Companies in Indonesia - Sofiyah, Yuni (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The taxation of multinational corporations in Indonesia has a complex legal framework that integrates with international regulations. This article discusses various provisions governing taxes for companies operating in more than one country, including the obligation to collect income tax (PPh), value-added tax (VAT), and to fulfill transparent financial reporting requirements. In Indonesia, multinational corporations must comply with the rules stipulated in the Tax Law and implement transfer pricing principles in line with OECD guidelines. This regulation introduces new provisions related to income tax, tax collection, and more transparent reporting obligations for foreign entities. One key point is the update on the global minimum tax, aimed at preventing tax avoidance and strengthening a fair tax system. Additionally, the law emphasizes the need to fulfill substance requirements for intercompany transactions to reduce the potential for harmful transfer pricing. Consequently, multinational companies are expected to operate more responsibly and in compliance with the established regulations while continuing to contribute to Indonesia's economic growth.